Impact of Tetranychus ogmophallos (Acari: Tetranychidae) on different phenological stages of peanuts - Melville, Cirano Cruz [UNESP]; Andrade, Samuel Carvalho [UNESP]; Oliveira, Natalia Trajano; Andrade Junior, Daniel [UNESP] (Inst Agronomico, 2018)
Peanut red mite, or Tetranychus ogmophallos Ferreira and Flechtmann, is considered the major emerging pest of peanut in Brazil. Its impact on peanut farming is still unknown but can be harmful. Thus, it is essential to understand how this mite influences peanut for a successful pest management program. This study aimed to investigate the impact of T. ogmophallos on peanut plants at different growth stages in order to clarify whether or not it is worth controlling this pest throughout the peanut growing season. For that, four experiments were carried out in a greenhouse to evaluate the impact of T. ogmophallos infestation on peanut plants at different phenological stages. Results showed that peanut seedlings of up to 60 days emergence and infested with red mite did not complete the reproductive cycle. In addition, infestation at 90 days after seedling emergence (late season) led to considerable yield reduction. As a result, we may infer that infestation can significantly peanut yield, regardless of plant phenological stage. Thus, controlling this emerging pest is necessary even if infestations occur in the final stages of plant development. The adopted level of infestation is above the economic threshold given the importance of the impact on growth and yield of these plants. Because of this, establishing an economic threshold level at different plant developmental stage is crucial to determine when control measures should be taken.
Keywords: peanut red mite; Arachis hypogaea; economic acarology; granoleico; fabaceae